2013
DOI: 10.1134/s1063778813100141
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of 10C nuclei in a track nuclear emulsion at an energy of 1.2 GeV per nucleon

Abstract: The charge topology in the fragmentation of 10 C nuclei in a track nuclear emulsion at an energy of 1.2 GeV per nucleon is studied. In the coherent dissociation of 10 C nuclei, about 82% of events are associated with the channel 10 C → 2α+ 2p. The angular distributions and correlations of product fragments are presented for this channel. It is found that among 10 C → 2α+ 2p events, about 30% are associated with the process in which dissociation through the ground state of the unstable 9 Beg.s. nucleus is follo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The values pβc4 He were measured for H and He tracks of 16 "white" stars 10 C → 2He + 2H in the NTE exposed to a mixed beam of isotopes 7 Be, 10 C and 12 N [ [25][26][27] with the same momentum per nucleon as in the case of 9 C. The dominance of 1 H and 4 He isotopes confirms the separation of 10 C (Fig. 7).…”
Section: Advantages Of the Nte Techniquementioning
confidence: 66%
See 1 more Smart Citation
“…The values pβc4 He were measured for H and He tracks of 16 "white" stars 10 C → 2He + 2H in the NTE exposed to a mixed beam of isotopes 7 Be, 10 C and 12 N [ [25][26][27] with the same momentum per nucleon as in the case of 9 C. The dominance of 1 H and 4 He isotopes confirms the separation of 10 C (Fig. 7).…”
Section: Advantages Of the Nte Techniquementioning
confidence: 66%
“…for events Z f r = 6 and 7 is shown in Fig. 6 [25][26][27]. In cases of light neutron-deficient nuclei the determination of charges allows one to determine their mass numbers.…”
Section: Advantages Of the Nte Techniquementioning
confidence: 99%
“…Contribution of the unstable nuclei 6 Be, 8 Be and 9 B into dissociation of relativistic nuclei 7,9 Be, 10 B and 10,11 C is under study on the basis of the nuclear track emulsion exposed to secondary beams of the JINR Nuclotron.…”
Section: Discussionmentioning
confidence: 99%
“…Their ratio is equal to 0.7 ± 0.1 [11]. Recently obtained statistics of 140 10 B "white" stars is presented in The unstable nuclei in dissociation of the 9 Be, 10 Earlier, basing on the Q αp energy distribution of the triples 2α + p from the "white" stars 10 C → 2α + 2p it is concluded that in the 10 C nucleus the core 9 B is manifested with a probability of 30 ± 4%, and the 8 Be g.s. decays are arise always through the 9 B…”
Section: Nuclear Clustering In Relativistic Dissociationmentioning
confidence: 98%
“…The interaction of virtual helium isotopes and neutron exchange between them in the 11 C nucleus lead to the formation of cluster structures, including the 2 4 He + 3 He configuration. Among them, configurations characterized by low binding energies, such as 7 Be + α (7.6 MeV), 10 B + p (8.7 MeV) and 3 He + 8 Be (9.2 MeV), are expected to be more probable than the 9 9 Be + 2p (15.3 MeV) and 8 Because of a wide variety of virtual cluster configurations that may exist in the structure of the 11 C nucleus, investigation of this nucleus becomes an interesting problem in and of itself.…”
mentioning
confidence: 99%